Quantum mechanics in chemistry - Schatz, George C., 1949- (Dover Publications, 2002)
Advanced graduate-level text looks at symmetry, rotations, and angular momentum addition; introduces basic formalism of time-dependent quantum mechanics and occupation number representations; focuses on scattering theory; uses its concepts to develop basic theories of chemical reaction rates, and more. Problems appear at end of each chapter; solutions included.
Originally published: Englewood Cliffs, N.J. : Prentice Hall, c1993.
"A new appendix C, Solutions to problems, has been specially prepared by the authors for this edition"--T.p. verso.
Keywords: Quantum chemistry.; Quantum theory.; elektronické knihy; electronic books